Eco-innovation and business performance in emerging and developed economies - Lopes Santos, David Ferreira [UNESP]; Valente Rezende, Maitê Dubugras [UNESP]; Cruz Basso, Leonardo Fernando (Elsevier, 2019)
This study initially explored 323 sustainability reports certified by the Global Reporting Initiative. The aim was to evaluate, at the company level, the structure of eco-innovation of firms established in developed and emerging countries and the influence of eco-innovation on the financial performance of those companies during the 2012–2014 period. A sample of 231 companies was collected, 58 from emerging countries and 173 from developed countries. The methodology was based on structural equation modeling and regression with panel data. The study revealed that nearly all environmental and social eco-innovation variables were significant in their respective dimensions in the developed countries, whereas in the emerging countries, only two environmental and social variables were significant, thus highlighting the more advanced stage of eco-innovation in developed countries. The results of the regression with panel data indicated that the environmental and social variables were significant only for return on sales (ROS) and differed between companies located in emerging and developed countries.
Keywords: Business results; Environmental impact; Innovation capacity; Sustainable innovation